2015
DOI: 10.2196/jmir.3388
|View full text |Cite
|
Sign up to set email alerts
|

SimQ: Real-Time Retrieval of Similar Consumer Health Questions

Abstract: BackgroundThere has been a significant increase in the popularity of Web-based question-and-answer (Q&A) services that provide health care information for consumers. Large amounts of Q&As have been archived in these online communities, which form a valuable knowledge base for consumers who seek answers to their health care concerns. However, due to consumers’ possible lack of professional knowledge, it is still very challenging for them to find Q&As that are closely relevant to their own health problems. Consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The proposed corpus consists of questions which can be answered using EHR data. Such a corpus would have utility beyond QA systems as well, like in question similarity (Luo et al, 2015;Nakov et al, 2017), and in particular could serve as a standard paraphrase corpus for the medical domain.…”
Section: Paraphrasing For Question Answeringmentioning
confidence: 99%
“…The proposed corpus consists of questions which can be answered using EHR data. Such a corpus would have utility beyond QA systems as well, like in question similarity (Luo et al, 2015;Nakov et al, 2017), and in particular could serve as a standard paraphrase corpus for the medical domain.…”
Section: Paraphrasing For Question Answeringmentioning
confidence: 99%
“…Cohen and colleagues have shown that interactive question answering sites could efficiently address consumer health question answering through either short answers by a small number of dedicated physicians, enabling high throughput, or physician experts operating as moderators in patient forums [102]. Luo and colleagues used syntactic and semantic analysis to align a new question with the questions previously submitted to NetWellness, a website through which highly qualified volunteers provide answers to consumers' health questions [103].…”
Section: Understanding Consumer Health Questions Onlinementioning
confidence: 99%
“…RQE is particularly relevant due to the increasing numbers of similar questions posted online [32] and its ability to solve differently the challenging issues of question understanding and answer extraction. In addition to being used to find relevant answers, these resources can also be used in training models able to recognize inference relations and similarity between questions.…”
Section: Introductionmentioning
confidence: 99%